PENERAPAN PEMBELAJARAN BERDIFERENSIASI BERBANTUAN MEDIA ASSEMBLR EDU BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Harfiani, Dani Rahma; Wulandari, Desi; Safitri, Rani Dwi; Sayektiningsih, Sayektiningsih (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
In the digital age, educational challenges include the integration of technology by teachers to meet the diverse needs of students. Many teachers still find it difficult to update their knowledge and skills as technology evolves. This hinders the achievement of the desired independent learning. The study aims to identify progress in the learning achievement of grade IV-B students through the application of a differentiated learning approach using augmented reality-based edu assemblr media in science subjects at SDN Gisikdrono 02 Semarang City. This study uses a classroom action research approach consisting of two cycles with four stages, namely: 1) planning, 2) implementation, 3) observation, 4) reflection. The subjects of this study were 27 students of grade IV-B of SD Negeri Gisikdrono 02. The data collection techniques used are interviews, observations, tests, and documentation. The results showed that the use of Assemblr Edu media based on Augmented Reality improved student learning outcomes. This can be seen from the acquisition of teacher activity scores in cycle I, which was 78.06 (sufficient) increased to 83.23 (Good) in cycle II. The learning outcomes of grade IV-B students on culturally rich Indonesian material have increased after using augmented reality-based edu assemblr media. This can be seen from the increase in the percentage of completeness of student learning outcomes in cycle I, namely 63% (less) to 85.2% (good) in cycle II